Exploring Cyberlaw and Framework Research Trends: A Data Analysis - Amelya, Anggita Diva; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This data article presents an analysis of research trends in the field of cyberlaw and framework, conducted by filtering data through the Lens.org database with the keyword 'cyberlaw and framework,' subject filter 'law,' and document type 'journal article.' The data is beneficial for understanding the landscape of journal articles addressing cyberlaw and framework, making it a valuable resource for students and researchers seeking information on this topic. The primary objectives are to determine the volume of journal articles on cyberlaw and framework, identify prolific institutions, active countries, and prominent publishers within the field. The data reveals annual publication trends, highlights active institutions by discipline, showcases prolific authors, and presents valuable insights into the most prominent publishers. This comprehensive analysis provides a snapshot of the current state of research in cyberlaw and framework, serving as a valuable resource for scholars and professionals alike. Highlight: Artificial Intelligence (AI) is rapidly advancing, impacting various aspects of our lives. Ethical implications arise as AI and machine learning make decisions affecting individuals and society. Ensuring data security and addressing privacy concerns are critical in AI development. Keywords: Artificial Intelligence, Ethical Implications, Machine Learning, Privacy Concerns, Data Security